Drug repurposing using meta-analysis of gene expression in Alzheimer’s disease - Jang, Ha Young; Oh, Jung Mi; Kim, In-Wha (Frontiers in Neuroscience, 2022)
Introduction: Alzheimer's disease and other forms of dementia are disease that bring an increased global burden. However, the medicine developed to date remains limited. The purpose of this study is to predict drug repositioning candidates using a computational method that integrates gene expression profiles on Alzheimer’s disease and compound-induced changes in gene expression levels. Methods: Gene expression data on Alzheimer’s disease were obtained from the Gene Expression Omnibus (GEO) and we conducted a meta-analysis of their gene expression levels. The reverse scores of compound-induced gene expressions were computed using the Library of Integrated Network-based Cellular Signatures (LINCS). Results: Reversal genes and the candidate compounds were identified by the leave-one-out cross-validation procedure. Additionally, the half-maximal inhibitory concentration (IC50) values and the blood-brain barrier (BBB) permeability of candidate compounds were obtained from ChEMBL and PubChem, respectively. Conclusion: New therapeutic target genes and drug candidates against Alzheimer’s disease were identified by means of drug repositioning.